Pengaruh Problematic Internet Use terhadap Perilaku Cyberbullying pada Remaja Akhir Pelaku Cyberbullying - Qonita Tsaltsa Earlyana; Sulisworo Kusdiyati (UNISBA Press, 2023)
Abstract. The COVID-19 pandemic has had a major impact on every aspect of human life. Technology is the main need for humans to carry out activities during the implementation of the lockdown to suppress the spread of COVID-19. Adolescents are one of the most vulnerable age groups to this lifestyle change. Internet use is increasing among adolescents, and this can trigger psychological problems experienced by adolescents, such as stress, anxiety, depression, psychological pressure, emotional problems, and problematic internet use. Problematic internet use involves loss of control over internet use, cognitive impairment associated with internet use, and persistent internet use behaviours that harm daily life. This study aims to determine the effect of problematic internet use behaviour on cyberbullying in late teens who are cyberbullying perpetrators in West Java. This study uses a quantitative causality correlation method. The measuring instruments used in this study were the Generalized Problematic Internet Use Scale 2 (GPIUS2) by Caplan and the Cyberbullying Offending Scale by Patchin & Hinduja. This research was given to 120 teenagers in West Java, who were obtained using a quota sampling technique. The analysis technique used is a simple regression analysis technique. According to the findings of this study, problematic internet use reduces cyberbullying by 15.7% (p.05). In addition, the time spent using the internet can affect teenagers' problematic internet use (Sig .045<.05). Keywords: Problematic Internet Use, Cyberbullying, Late Adolescence, COVID-19. Abstrak. Pandemi COVID-19 berdampak besar di setiap aspek kehidupan manusia. Teknologi menjadi kebutuhan utama manusia untuk beraktivitas di tengah pemberlakuan lockdown diterapkan untuk menekan angka penyebaran COVID-19. Remaja merupakan salah satu kelompok usia yang rentan dengan perubahan gaya hidup ini. Penggunaan internet semakin meningkat di kalangan remaja dan hal tersebut dapat memicu masalah-masalah psikologis yang dialami remaja, seperti stress, kecemasan, depresi, tekanan psikologis, masalah emosional, dan penggunaan internet yang bermasalah atau problematic internet use. Problematic internet use melibatkan hilangnya kontrol atas penggunaan internet, gangguan kognitif terhadap penggunaan internet, dan perilaku penggunaan internet yang berkelanjutan hingga menimbulkan dampak buruk pada kehidupan sehari-hari. Penelitian ini bertujuan untuk mengetahui pengaruh problematic internet use terhadap perilaku cyberbullying pada remaja akhir pelaku cyberbullying di Jawa Barat. Penelitian ini menggunakan metode korelasi kausalitas kuantitatif. Alat ukur yang digunakan pada penelitian ini adalah Generalized Problematic Internet Use Scale 2 (GPIUS2) dari Caplan dan Cyberbullying Offending Scale dari Patchin & Hinduja. Penelitian ini diberikan kepada 120 remaja di Jawa Barat yang diperoleh menggunakan teknik quota sampling. Teknik analisis yang dipakai adalah teknik analisis regresi sederhana. Hasil penelitian ini menunjukkan bahwa problematic internet use berpengaruh positif terhadap perilaku cyberbullying sebesar 15.7% (p<.05). Selain itu, waktu dalam menggunakan internet dapat mempengaruhi remaja mengalami problematic internet use (Sig .045<.05). Kata Kunci: Problematic Internet Use, Cyberbullying, Remaja Akhir, COVID-19.